Calcium supplementation for the prevention of hypertensive disorders of pregnancy: current evidence and programmatic considerations. Issue 1 (8th January 2022) - Gomes, Filomena; Ashorn, Per; Askari, Sufia; Belizan, Jose M.; Boy, Erick; Cormick, Gabriela; Dickin, Katherine L.; Driller‐Colangelo, Amalia R.; Fawzi, Wafaie; Hofmeyr, G. Justus; Humphrey, Jean; Khadilkar, Anuradha; et al.
Abstract: Most low‐ and middle‐income countries present suboptimal intakes of calcium during pregnancy and high rates of mortality due to maternal hypertensive disorders. Calcium supplementation during pregnancy is known to reduce the risk of these disorders and associated complications, including preeclampsia, maternal morbidity, and preterm birth, and is, therefore, a recommended intervention for pregnant women in populations with low dietary calcium intake (e.g., where ≥25% of individuals in the population have intakes less than 800 mg calcium/day). However, this intervention is not widely implemented in part due to cost and logistical issues related to the large dose and burdensome dosing schedule (three to four 500‐mg doses/day). WHO recommends 1.5–2 g/day but limited evidence suggests that less than 1 g/day may be sufficient and ongoing trials with low‐dose calcium supplementation (500 mg/day) may point a path toward simplifying supplementation regimens. Calcium carbonate is likely to be the most cost‐effective choice, and it is not necessary to counsel women to take calcium supplements separately from iron‐containing supplements. In populations at highest risk for preeclampsia, a combination of calcium supplementation and food‐based approaches, such as food fortification with calcium, may be required to improve calcium intakes before pregnancy and in early gestation. Abstract : In early 2021, the Nutrition Science Program of the New York Academy of Sciences convened a Calcium Task Force to assess the evidence on global calcium deficiency and its health consequences. This paper describes the task force's discussions and conclusions with regard to calcium supplementation for the prevention of hypertensive disorders of pregnancy, with a major focus on preeclampsia.